Granulocyte-macrophage colony-stimulating factor (GM-CSF) allows acceleration and dose intensity increase of CEF chemotherapy: a randomised study in patients with advanced breast cancer. - Ardizzoni, A. (Nature Publishing Group, 1994)
A randomised study was conducted in 62 patients with advanced breast cancer to assess whether granulocyte-macrophage colony-stimulating factor (GM-CSF) would yield an increase in the dose intensity of a standard-dose CEF regimen through an acceleration of chemotherapy administration. Patients received CEF (cyclophosphamide 600 mg m-2, epidoxorubicin 60 mg m-2 and fluorouracil 600 mg m-2) i.v. on day 1 or the same chemotherapy, plus GM-CSF 10 micrograms kg-1 s.c. starting from day 4, repeated as soon as haematopoietic recovery from nadir occurred. Patients in the CEF + GM-CSF group received chemotherapy at a median interval of 16 days compared with 20 days in the control group. This led to a significant increase (P = 0.02) in the dose intensity actually administered in the third, fourth and sixth cycles: +28%, +25%, +20% respectively. Non-haematological toxicity was mild. GM-CSF had to be reduced or suspended in 50% of patients because of toxicity. Haematological toxicity, mainly cumulative anaemia and thrombocytopenia, was manageable. An increase in response rate for patients with measurable disease, of borderline statistical significance (P = 0.088, P for trend = 0.018), from 42% in the CEF group to 69% in the CEF + GM-CSF group, was observed. This randomised trial indicates that GM-CSF is useful for chemotherapy acceleration. Accelerated CEF + GM-CSF is a moderately dose-intensive regimen that can be administered in an outpatient clinic and is associated with a high objective response.